Channels and processes of knowledge transfer: How does knowledge move between university and industry?. (3rd February 2020) - Fabiano, Gianluca; Marcellusi, Andrea; Favato, Giampiero
Abstract: The role of knowledge and technology transfer between academia and the industry has received increasing attention in the analysis of innovation. This article aims to explore the scientific literature concerning knowledge transport mechanisms and describe how the topic was organized by previous studies and terminologies applied. A systematic review was conducted in which the content of recent contributions best fitting these intensions was analysed. The characteristics of knowledge, individuals, organizations, and disciplines were found to be the main determinants in the adoption of transfer mechanisms. These were classified in terms of formalization, relational involvement, direction, and time. On the revealed multi-dimensionality of knowledge transfer and complementarity between transfer activities we framed a new taxonomy distinguishing between channels and processes. Future research may deepen these factors, such as the economic aspects driving the adoption of transfer mechanisms informing decisions on the funding of innovation.